Weed Control in Corn and Soybean with Group 15 (VLCFA Inhibitor) Herbicides Applied Preemergence - Nader Soltani; Lynette R. Brown; Peter H. Sikkema (International Journal of Agronomy)
Limited information exists on the efficacy of pethoxamid for annual grass and broadleaf control in corn and soybean in Ontario. A total of 10 field experiments (5 with corn and 5 with soybean) were conducted during 2015 to 2017 in Ontario, Canada, to compare the weed control efficacy of dimethenamid-P at 544 g·ai·ha−1, pethoxamid at 840 g·ai·ha−1, pyroxasulfone at 100 g·ai·ha−1, and S-metolachlor at 1050 g·ai·ha−1 applied preemergence (PRE). Reduced weed interference with pyroxasulfone and dimethenamid-P resulted in corn yield that was similar to the weed-free control; however, weed interference with pethoxamid and S-metolachlor reduced corn yield 28 and 33%, respectively. Reduced weed interference with pyroxasulfone resulted in soybean yield that was similar to the weed-free control; however, weed interference with pethoxamid, dimethenamid-P, and S-metolachlor reduced soybean yield 27, 27, and 30%, respectively. At 4 and 8 weeks after application (WAA), all VLCFA inhibitor herbicides (Group 15) provided excellent redroot pigweed control (90 to 99%) in corn. There were no differences in common ragweed control, density, and dry weight among the VLCFA inhibitor herbicide evaluated; pyroxasulfone provided highest numeric common ragweed control and lowest numeric density and dry weight. At 4 and 8 WAA, pyroxasulfone provided the best common lambsquarters and wild mustard control and lowest numeric density and dry weight in corn and soybean. At 8 WAA, the VLCFA inhibitor herbicides controlled green foxtail 91 to 96% in corn; dimethenamid-P provided better control of green foxtail than pethoxamid in soybean. There were no differences in barnyard grass control among the VLCFA inhibitor herbicides evaluated.